The impact of gifts and shared experiences on an investor-manager relationship - Maximilian Hoyer; Frans A. A. M. van Winden (Games, 2025)
This paper experimentally investigates the relationship between an investor and a project manager. Project managers choose from a pool of projects, the success probabilities of which are uncertain. Investors can change projects, but also have to change project managers if they want to do so. An additional joint project or a voluntary money transfer precedes their interaction. We hypothesize that investors favor projects of managers with whom they share positive experiences at that stage, even though these experiences do not provide any information about the subsequent project's success probability. Interaction through a voluntary transfer plays a clear and significant role in the investors' decision-making via bonding, whereas the influence of merely sharing a positive or negative experience proves more complex.
Keywords: D01; D91; G00; G41; M12; M51; 330; investor-manager relationship; experiment; affective ties; investment; gift